Surface water quality assessment of the Gebeng industrial area using water quality standard and index - Islam, Mir Sujaul; Salah, M. G; Arafat, Md. Yasir; Abdul Syukor, Abd Razak; A., Idris (RMP Publications, 2017)
Surface water is a quick impact of pollution because of their easy accessibility for disposal of wastewater. Natural processes and industrial activities determine the quality of surface water in a region. The study was done to evaluate the surface water quality of Gebeng industrial estate, Pahang, Malaysia. Ten stations were established along the Tunggak and Balok River to collect water samples. The data were calculated according to Water Quality Index which obtained by Department of Environment (WQI-DOE) and categorized to compare with National Water Quality Standard Malaysia (NWQS). Water quality of Gebeng was classified based on WQI Malaysia as class III (51.9 – 76.5), and IV (< 51.9) which are slightly polluted and polluted due to low levels of DO and pH, and high levels of AN, BOD, COD, and TSS. It is clear that stations IZ2, IZ3, HA1, HA2, DS are received the largest pollutants discharged from the industrial sector. Generally, the results of this study will be very useful for policy maker and future studies to control and management of pollution in the study area.